(untitled) (Sustainability in Debate, 2018)
Initiatives aimed at the conservation of Protected Areas (PAs) stand out as essential actions for the protection of the natural environment and its elements. This study aims to analyze strategies related to environmental conservation in the Private Reserves of Natural Heritage (RPPNs) Quinta do Sol and Vale do Bugio, in the Mato Grosso do Sul State. The research was conducted with a quali-quantitative and multidisciplinary approach. Twelve variables compatible with the two reserves were verified as environmental sustainability indicators. The propagation of environmental conservation strategies used by these reserves can contribute significantly to the expansion of new protected areas in important regions, as is the case of Serra de Maracaju, a priority area for biodiversity conservation.